2015
DOI: 10.1002/2014jc010668
|View full text |Cite
|
Sign up to set email alerts
|

Beam attenuation, scattering and backscattering of marine particles in relation to particle size distribution and composition in Hudson Bay (Canada)

Abstract: This study investigated the relationships between the concentration of biogeochemical parameters and particulate beam attenuation (c p ), scattering (b p ), and backscattering (b bp ) in Hudson Bay. Results showed that most of the variability resulted from the presence of a deep chlorophyll maximum. c p , b p , and b bp were all adequate proxies to estimate total suspended matter (TSM) but were mostly sensitive to particulate inorganic matter (PIM) in the surface layer, and particulate organic matter (POM) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
(164 reference statements)
4
14
0
Order By: Relevance
“…At LJCO our observations of type 2 waters are similar, while type 1 waters show values lower than these theoretical predictions (Figure ). However, lower than 0.02 values of backscattering ratio are theoretically predicted (Duforêt‐Gaurier et al, ; Twardowski et al, ) and observed (Boss et al, ; Loisel et al, ; McKee & Cunningham, ; Snyder et al, ; Whitmire et al, ; Xi et al, ) in regions dominated by phytoplankton and organic detritus and recently also found in the waters of Yellow and East China Seas dominated on average by 80% of inorganic particles (Sun et al, ). Microscopic imaging of mineral/organic flocs in our study area (Bainbridge et al, ) shows complex particle geometries, which may explain the difference from idealized theoretical prediction based on more regular geometry and no organic matter.…”
Section: Discussionmentioning
confidence: 88%
“…At LJCO our observations of type 2 waters are similar, while type 1 waters show values lower than these theoretical predictions (Figure ). However, lower than 0.02 values of backscattering ratio are theoretically predicted (Duforêt‐Gaurier et al, ; Twardowski et al, ) and observed (Boss et al, ; Loisel et al, ; McKee & Cunningham, ; Snyder et al, ; Whitmire et al, ; Xi et al, ) in regions dominated by phytoplankton and organic detritus and recently also found in the waters of Yellow and East China Seas dominated on average by 80% of inorganic particles (Sun et al, ). Microscopic imaging of mineral/organic flocs in our study area (Bainbridge et al, ) shows complex particle geometries, which may explain the difference from idealized theoretical prediction based on more regular geometry and no organic matter.…”
Section: Discussionmentioning
confidence: 88%
“…For instance, phytoplankton functional types usually vary with size, a finding that has been incorporated into global biogeochemical models and used to assess the ecological feedback to the ocean's carbon In this study, we investigate the variability in PSD in two typically shallow and semi-enclosed seas, the Bohai Sea (BS) and the Yellow Sea (YS), with the following two objectives: (1) to model the PSD of the surface waters; and (2) to characterize the spatial variability and vertical distributions of the PSD. The potential findings by this study are very significant for understanding and documenting the particle size distributions in the BS and the YS, which have been regarded as important factors influencing water inherent optical properties [11,[40][41][42][43], and further changing water color remote sensing signals [44].…”
Section: Introductionmentioning
confidence: 92%
“…A Wetlabs ac‐s was used to collect profiles of total nonwater beam attenuation, c pg ( λ), absorption, a pg ( λ), and dissolved absorption, a g ( λ), at 86 spectral channels between 400 nm and 737 nm with a spectral resolution of 4 nm and a measurement accuracy ± 0.01 m −1 . Di‐ionized water and air calibrations were performed on this instrument before, during and after data collection periods to ensure instrument precision remained within factory specifications (Xi et al ). On each sampling day, approximately every fourth cast was performed with a 0.2 μm filter attached to the absorption tube of the ac‐s to measure a g ( λ).…”
Section: Methodsmentioning
confidence: 99%
“…The reported precision error of the calibrated ac‐s is ± 0.005 m −1 (Wetlabs 2015), which we ensured was maintained through water and air calibrations (section Optical profile data analysis). Under low scattering conditions, b p error can be as high as 18% (Piskozub et al ; Martinez‐Vincente et al ; Xi et al ). Error should be lower in our study due to relatively large b p magnitudes.…”
Section: Methodsmentioning
confidence: 99%